Phase Ib with expansion study of olaparib plus weekly (Metronomic) carboplatin and paclitaxel in relapsed ovarian cancer patients. Issue 2 (29th January 2019) - Rivkin, Saul Eugene; Moon, James; Iriarte, Desiree S; Bailey, Erik; Sloan, Heather L; Goodman, Gary E; BonDurant, Amy E; Velijovich, Dan; Wahl, Tanya; Jiang, Peter; Shah, Chirag A; Drescher, Charles; et al.
Abstract : Objective: Our goals were to: establish the maximum-tolerated dose of olaparib tablets combined with metronomic carboplatin and paclitaxel in patients with relapsed high-grade serous ovarian cancer; evaluate dose-limiting toxicities; and evaluate efficacy at the maximum tolerated dose. Methods: In this open-label, single-arm, investigator-initiated trial (ClinicalTrials.gov NCT01650376 ), patients with high-grade serous ovarian cancer who failed primary platinum and taxane therapy received oral olaparib tablets twice daily days 1–3 each week combined with fixed-dose metronomic carboplatin AUC2 and paclitaxel 60 mg/m 2 weekly for 3 out of 4 weeks. A 3 × 3 design was used to determine the olaparib maximum tolerated dose. Combination therapy continued until disease progression, but patients with partial or complete response were transitioned to olaparib maintenance therapy. All patients were included in the analysis. Results: The maximum tolerated dose of olaparib tablets was 150 mg twice daily with metronomic carboplatin and paclitaxel. 54 women were enrolled, 14 in phase Ib and 40 in the expansion phase. The median number of prior therapeutic regimens was 3. Response included 13 complete remission (24%) and 16 partial remission (30%) per Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1) for an overall response rate of 54% (95% CI 40% to 67%). Of 47 patients who underwent BRCA testing, 23 were BRCA mutation ( BRCAm ) and 24 B RCA wild type ( BRCAwt ). Progression-free survival for BRCAm was 12.1 months versus 4.8 for BRCAwt (p=0.0001). Median overall survival for BRCAm was 24.1 months versus 10.4 months for BRCAwt (p=0.02). 42 patients (78%) experienced grade 3–4 toxicities with combination therapy; the most common were hematologic. There were no treatment related deaths. Among 14 patients who received maintenance therapy, 7 experienced grade 1–2 non-hematologic toxicities. Conclusions: Olaparib 150 mg tablet twice daily can be safely administered in combination with metronomic carboplatin and paclitaxel in pre-treated relapsed ovarian cancer with 24% complete remission. BRCAm patients had statistically significant longer progression-free survival and overall survival than BRCAwt . Trial registration number: NCT01650376 .